Identifying pragmatic solutions to reduce cigarette smoking prevalence in Indigenous North Americans: A sequential exploratory mixed-methods study protocol. - Ann M Rusk; Maggie Paul; Dan P Kelleher; Jon Tilburt; Donald Northfelt; Matthew Rank; Rodrigo Cartin-Ceba; Guthrie Capossela; Trudie Jackson; Corinna Sabaque; Alanna M Chamberlain; Victor E Ortega; et al. (PLoS ONE)
Background American Indians and Alaska Natives (AI/AN) have the highest prevalence of cigarette smoking of any race or ethnicity in the United States. Efforts to address smoking prevalence in this population have not historically targeted maintenance of smoking cessation, or behaviors associated with pregnancy. Recent longitudinal cohort studies have identified maintenance of cessation and pregnancy as potential opportunities to address smoking in AI/AN people. Methods To promote success in achieving sustained smoking cessation in AI/AN people, we propose a community engaged sequential exploratory mixed-methods study focused on identifying pragmatic elements of cessation interventions. A discovery sample of 45 AI/AN people will be included in the qualitative study in one of two arms consisting of small groups or one-on-one interviews to develop elements of cessation interventions for evaluation in a discrete choice experiment survey. These one-on-one interviews will characterize the key drivers of smoking relapse and unique experiences of smoking during pregnancy. An additional, independent small group will consist of counselors who engage in smoking cessation counseling. A larger-scale survey will be administered to an AI/AN cohort from Olmsted County, Minnesota (n = 898). Elements of successful interventions will be used to inform a smoking cessation intervention pilot study. Community stakeholders have informed the methods outlined in this protocol, and there is a longitudinal engagement plan for the duration of study. Discussion We outline the methods to understand optimal strategies to promote sustained cigarette smoking cessation and cessation during pregnancy in AI/AN people. This study is critical to inform a pilot intervention aimed at reducing smoking prevalence in AI/AN people.